Pengaruh Penggunaan Media Diorama terhadap Kemampuan Bercerita di Taman Kanak-Kanak - Novita, Selvira; Yetti, Rivda; Wirman, Asdi (Penerbit Aksara Rentaka Siar (ARS), 2019)
This research was conducted with the aim to determine how much influence the use of diorama media in honing the ability to tell stories in the Research Park used a quantitative approach to the type of Quasy Experiment by using the media diorama. Data collection techniques used tests and data collection tools used observation sheets. Based on the results of the data analysis, the average test results of the experimental group with diorama media with the control group with conventional activities were found to be 74.79 and 68.54 respectively. Based on these results it was concluded that the diorama media influenced the ability of children's stories in Mutiara Al Madani Kindergarten in Gedang Sungai Penuh City.